Diabetic Shoes with Foot Moisture Detection System to Support the Foot Care of Diabetic Patients - Defrima Oka Surya; Ria Desnita; Anugrah Ilahi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Diabetic Foot Ulcers (DFU) are one of the serious complications experienced by diabetes patients. Foot care for DM patients is very important to prevent foot ulcer complications. Foot care can be done by using the right shoes and also maintaining moisture on the foot skin. Wearing shoes for too long affects the moisture of the feet. Skin that is too dry or too moist can also cause damage to the skin, which can lead to ulcers. Special shoes for DM patients that have already been used still have limitations and do not monitor foot health optimally and in real-time. The aim of this research is to design diabetes shoes with a foot moisture detection system. The design of this research is a research and development approach (R&D). The stages conducted in this research consist of literature study, system design, design implementation, system testing, and analysis. Data analysis and system performance results will evaluate the sensor's function to detect foot moisture in patients while using the shoes. The result of this research is the development of diabetes shoes with a real-time moisture detection system. It is hoped that diabetes mellitus patients can independently perform foot care, one of which is by controlling foot moisture.